Il richiamo “epistemologico” della fraternità. L’avventura educativa di abitare la Terra - Simona Sandrini (Studi sulla Formazione, 2022)
One year after the first United Nations Conference held in Rio de Janeiro in 1992 on Environment and Development, Edgar Morin in his book Terre-Patrie (1993) underlines the relation between human suffering and natural cataclysms. The ecological crisis motivates his call to care for the Earth, requiring to become conscious that the common destiny of all the humanity must be interpreted as a ‘‘terrestrial’’ destiny. The reference to the principle of fraternity expressed in 1993 is explored further in La Fraternité, pourquoi? (2020). Fraternity as a driver can become an educational path for the human adventure in this ‘planetary era’.